2006
DOI: 10.1097/01.ta.0000197180.79965.bc
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Interleukin-10 in the Assessment of Venous Thromboembolism Risk in Injured Patients

Abstract: An elevated sP-selectin to IL-10 ratio appears to be associated with the development of VTE in patients at high risk and may prove to be a useful clinical marker for this dreaded complication among trauma patients. Early recognition of this high-risk group improves the accuracy of the risk/benefit determination for prophylaxis and identifies a group in whom routine ultrasound screening would be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The sP-selectin level difference was not statistically significant between the groups. Those patients who developed VTE had a higher sP/IL-10 ratio, where lower levels of IL-10 accounted for the ratio-difference, statistically significant to those without VTE ( 61 ).…”
Section: Adhesion Molecules and Vtementioning
confidence: 96%
See 1 more Smart Citation
“…The sP-selectin level difference was not statistically significant between the groups. Those patients who developed VTE had a higher sP/IL-10 ratio, where lower levels of IL-10 accounted for the ratio-difference, statistically significant to those without VTE ( 61 ).…”
Section: Adhesion Molecules and Vtementioning
confidence: 96%
“…A number of small case-control studies demonstrated increased levels of pro-inflammatory, or decreased levels of anti-inflammatory, cytokines in patients at risk for DVT ( 61 , 63 , 45 ). Although in a larger, prospective population-based case-control study, no such associations were found ( 37 ).…”
Section: Cytokines and Vtementioning
confidence: 99%
“…A study by Proctor et al (19) indicated that IL-10 could be an important clinical predictor of thrombosis. IL-10 has also been found to exert anticoagulant properties (20).…”
Section: Discussionmentioning
confidence: 99%
“…An increased P-selectin/IL-10 ratio was found to be a risk factor for venous thrombosis in trauma patients (149), whereas selected haplotypes of selectins were not found to influence DVT risk in a large population-based study (173). Several studies have demonstrated increased P-selectin levels in VTE patients, both when compared to normal controls and as a diagnostic marker in symptomatic patients (154,171,172,(174)(175)(176)(177)(178)(179).…”
Section: Adhesion Molecules In Venous Thrombosismentioning
confidence: 99%
“…Inflammatory conditions are considered as a risk factor for venous thromboses (138)(139)(140)(141). However, some larger studies of altered inflammatory mediators indicated that both changes in inflammatory mediator levels -TNF- (149,150) and several SNPs of inflammatory mediators are associated with an IL-1 IL-IL-6, IL-10) (141,145).…”
Section: Inflammation-cause or Consequence?mentioning
confidence: 99%